2007
DOI: 10.1073/pnas.0705003104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p21-activated kinase rescues symptoms of fragile X syndrome in mice

Abstract: Fragile X syndrome (FXS), the most commonly inherited form of mental retardation and autism, is caused by transcriptional silencing of the fragile X mental retardation 1 (FMR1) gene and consequent loss of the fragile X mental retardation protein. Despite growing evidence suggesting a role of specific receptors and biochemical pathways in FXS pathogenesis, an effective therapeutic method has not been developed. Here, we report that abnormalities in FMR1 knockout (KO) mice, an animal model of FXS, are ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
238
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(258 citation statements)
references
References 37 publications
17
238
2
1
Order By: Relevance
“…88 In addition, a recent study has shown that the genetic inhibition of a different kinase, p21-activated kinase, in the forebrain of Fmr1-null mice can fully or partially restore alterations in behavior and dendritic spine morphology. 60 These results demonstrate that gene interaction approaches can be used for the rescue, as well as the exacerbation, of specific endophenotypes relevant to neurodevelopmental disorders. However, transgenic overexpression of Mecp2 347 or Fmr1 58 in mice has been linked to detrimental effects, providing evidence that alterations of tightly regulated gene expression may have undesired consequences.…”
Section: Discussionmentioning
confidence: 85%
“…88 In addition, a recent study has shown that the genetic inhibition of a different kinase, p21-activated kinase, in the forebrain of Fmr1-null mice can fully or partially restore alterations in behavior and dendritic spine morphology. 60 These results demonstrate that gene interaction approaches can be used for the rescue, as well as the exacerbation, of specific endophenotypes relevant to neurodevelopmental disorders. However, transgenic overexpression of Mecp2 347 or Fmr1 58 in mice has been linked to detrimental effects, providing evidence that alterations of tightly regulated gene expression may have undesired consequences.…”
Section: Discussionmentioning
confidence: 85%
“…Adult Fmr1 KO mice and WT siblings were provided by the Tonegawa and Bear laboratories at the Picower Centre for Learning and Memory, Massachusetts Institute of Technology (MIT, Cambridge, MA). Animals were genotyped in MIT, as previously described (37). They were housed with siblings with a 14-h/10-h day/night cycle with ad libitum access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we will use the term abnormal repetitive behaviour (ARB) to encompass all of these. ARB can be induced in research animals via extreme early maternal deprivation [7], treatment with psychostimulant drugs [8,9], or genetic manipulations, as in DAT knockout [10] and Fragile X models [11]. In both humans and manipulated research animals, altered functioning of the basal ganglia and corticostriatal circuits is implicated in ARB.…”
Section: Introductionmentioning
confidence: 99%